Accelerating the activation of Li2MnO3 in Li-rich high-Mn cathodes to improve its electrochemical performance. Issue 9 (24th February 2021) - Huang, Chao; Fang, Zou-Qiang; Wang, Zhi-Jie; Zhao, Jian-Wei; Zhao, Shi-Xi; Ci, Li-Jie
Abstract : Morphology regulation and solid electrolyte coating are conducive to the activation of Li2 MnO3 phase for improving the electrochemical performance of Li-rich high-Mn oxides. Abstract : Li-rich high-Mn oxides, x Li2 MnO3 ·(1 − x )LiMO2 ( x ≥ 0.5, M = Co, Ni, Mn…), have attracted extensive research interest due to their high specific capacity and low cost. However, slow Li2 MnO3 activation and poor cycling stability have affected their electrochemical performance. Herein, to solve these problems, morphology regulation and LiAlF4 coating strategies have been synergistically applied to a Li-rich high-Mn material Li1.7 Mn0.8 Co0.1 Ni0.1 O2.7 (HM-811). This dual-strategy successfully promotes the activation process of the Li2 MnO3 phase and thus improves the electrochemical performance of HM-811. Theoretical computation indicates that the LiAlF4 layer has a lower Li + migration barrier than the HM-811 matrix, so it could boost the diffusion of Li + ions and promote the activation of the Li2 MnO3 phase. Benefiting from the morphology regulation and LiAlF4 coating, the HM-811 cathode shows a high initial charge capacity of >300 mA h g −1 . In addition, the modified HM-811 could deliver superior electrochemical performance even at a low temperature of −20 °C. This work provides a new approach for developing high performance cathode materials for next-generation Li-ion batteries.